Evaluation of antimicrobial activity of glycinate and carbonate derivatives of cholesterol: Synthesis and characterization - Rajendran Sribalan; Vediappen Padmini; Andiappan Lavanya; Kandasamy Ponnuvel (Elsevier, 2016)
A series of glycinate and carbonate derivatives of cholesterol (4a-t) were synthesized, characterized and assessed for their in vitro antimicrobial activity. Our results revealed that the compounds exerted inhibitory activities against gram-negative bacteria and fungi.